PENGARUH PRICE EARNING RATIO, ECONOMIC VALUE ADDED DAN MARKET VALUE ADDED TERHADAP HARGA SAHAM (Studi Kasus Pada Industri Minyak Dan Gas Yang Terdaftar di Bursa Efek Indonesia Periode 2018–2023) - Difiana Husein; Rizke Wiliyanti (ICMA Nasional, 2024)
This research aims to determine and examine the effect of Price Earning Ratio (PER), Economic Value Added (EVA), and Market Value Added (MVA) on stock prices in the Oil and Gas Industry listed on the Indonesia Stock Exchange, both partially and simultaneously during the 2018–2023 Period. The research population includes all oil and gas industry companies listed on the Indonesia Stock Exchange during the 2018-2023 period. The sample was determined using purposive sampling. Data analysis techniques use descriptive and verificative analysis with a quantitative approach. Hypothesis testing uses a multiple linear regression model and partial and simultaneous tests with IBM SPSS 23 software. The research results show that partially the Price Earning Ratio (PER) has an effect on stock prices, Economic Value Added (EVA) has an effect on stock prices. And Market Value Added (MVA) has an effect on stock prices. Meanwhile, simultaneously, Price Earning Ratio (PER), Economic Value Added (EVA) and Market Value Added (MVA)